PENGARUH PENGENDALIAN INTERNAL, KEPUASAN KERJA, MORALITAS MANAJEMEN, DAN BUDAYA ETIS ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - -, Julyana (Universitas Slamet Riyadi, 2015)
This study was aimed at discovering the perception of the financial workers in DPPKA’s in Surakarta regency about the effect of the internal control, job satisfaction, morality of management, and organization’s ethnic culture on the tendency of accounting fraud in DPPKAD Surakarta. This study was conducted with DPPKAs of the Surakarta, as one of the implementing lamenting of the region’s government in the form of office. The sampling technique used was census sampling. The sample consisted 97 workers in the office of the Surakarta’s. The data collection was done by distributing questionnaires with a set of question or statements to the respondents to be answered using Likert Scale. The data analysis techniques used were validity and reliability testing, Heteroscedasticity testing, Multicolinearity testing, Autocorelation testin, and normality testing, and then hypothesis testing using SPSS program 20.0 for windows. The results showed that: (1) there was a negative and not significnt effect between the internal control and tendency of accounting fraud in the DPPKA Surakarta, (2) there was a negative and not significant effect between the job satisfaction and tendency of accounting fraud in the DPPKA Surakarta, (3) there was a negative and significnt effect between the morality of management and tendency of accounting fraud in the DPPKA Surakarta, and (4) there was a negative and not significnt effect between the organization’s ethnic culture and tendency of accounting fraud in the DPPKA Surakarta. Keywords: tendency of accounting fraud, internal control, job satisfaction, morality of management, and organization’s ethnic culture.